2021
DOI: 10.1002/iid3.578
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the within‐subject (CVI) and between‐subject (CVG) biological variation of serum tryptase

Abstract: Background: Tryptase is used as a biomarker to support the diagnosis of anaphylaxis and hematologic diseases. In the event of a mast cell activation during anaphylaxis, a temporary increase in the concentration of tryptase may be seen. On the basis of clinical studies, an increase of 2 µg/L + 20% from basis level has been proposed as significant. To evaluate the increase in tryptase levels, the within-subject (CV I ) and between-subject (CV G ) biological variations should be known. This study was conducted to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Gonzalez-Quintela et al 4 Norway that BST levels are stable in healthy with a within-subject variation (CV i ) reported to 5.6%. 6 In the same study marked between-individual differences of BST levels were observed, with a between-subject variation (CV g ) reported to 31.5%. This underpins the importance of evaluating tryptase (in the case of suspected mast cell activation) using each individual's own baseline tryptase, as suggested by the consensus formula of a 20% + 2 μg/L increase from BST levels.…”
Section: Subjects (Location Number Of Participants) Assay Study Desig...mentioning
confidence: 78%
“…Gonzalez-Quintela et al 4 Norway that BST levels are stable in healthy with a within-subject variation (CV i ) reported to 5.6%. 6 In the same study marked between-individual differences of BST levels were observed, with a between-subject variation (CV g ) reported to 31.5%. This underpins the importance of evaluating tryptase (in the case of suspected mast cell activation) using each individual's own baseline tryptase, as suggested by the consensus formula of a 20% + 2 μg/L increase from BST levels.…”
Section: Subjects (Location Number Of Participants) Assay Study Desig...mentioning
confidence: 78%
“…The basal tryptase level is remarkably stable over time in individual healthy donors provided that no underlying disease associated with MC activation or MC expansion is present [ 16 , 17 , 18 •]. Moreover, in contrast to many other MC-derived mediators (histamine, PGD2, heparin, others), tryptase is a biologically stable protein that is not degraded, removed, or de-activated by changes in temperature, by other plasma proteins, or by short-term storage.…”
Section: The Basal Serum Tryptase Level In Healthy Controlsmentioning
confidence: 99%
“…However, the basal serum tryptase level varies among healthy individuals, depending on the genetic background, sex, age, kidney function, and presence of an underlying disease associated with MC expansion and/or activation [ 16 , 17 , 18 •].…”
Section: The Basal Serum Tryptase Level In Healthy Controlsmentioning
confidence: 99%
See 2 more Smart Citations